The Effect of Mushrooms Trichoderma sp. and Its Secondary Metabolites on Suppression of Fusarium sp. and Growth of Tomato Plants (Solanum lycopersicum mill.) - Agus Suyanto; Agnes Tutik Purwani Irianti; Hamdani Hamdani; Ismail Astar; Dwi Nurteto (International Journal of Multi Discipline Science, 2021)
This study aims to determine the interaction effect of the type and dose of Trichoderma sp. and its secondary metabolites on suppression of Fusarium sp. wilt disease and its effect on the growth of tomato plants (Solanum lycopersicum mill.). This study used a Randomized Block Design (RBD) which consisted of two factors. The first factor is the type of application (J) which consists of three levels of treatment, namely: J1 = Trichoderma sp., J2 = Secondary metabolites. J3 = Trichoderma sp. + Secondary metabolites, while the second factor is the application dose (D) which consists of three treatment levels, namely: D1 = 10 ml/plant, D2 = 20 ml/plant, D3 = 30 ml/plant. The treatment was repeated 3 times to obtain 81 tomato plants and added 9 control treatment plants. The parameters observed were the percentage of wilt disease, plant height, stem diameter, number of leaflets, and number of branches. The results showed that in laboratory testing, the mushrooms Trichoderma sp. and secondary metabolites can inhibit the growth of the mushrooms Fusarium sp. In research in the field, treatment with Trichoderma sp., secondary metabolites, and Trichoderma sp. + secondary metabolites, with various spore densities and applied 7 days before planting can reduce the wilting percentage to 0%. The interaction treatment of type and application dose had a very significant effect on the number of leaflets, and had a significant effect on stem diameter but had no significant effect on plant height and number of branches. The highest results on the variable plant height and number of leaflets were found in the J3D3 treatment with a height of 82.67 cm and a number of leaflets of 85.11 strands. The highest results on the stem diameter variable were found in the J1D3 treatment with a diameter of 6.59 mm, while the variable number of branches was found in the J3D1 treatment with 1.35 branches.